Biodiversity - The Dynamic Balance of the Planet 2014
DOI: 10.5772/58303
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Yeast Biodiversity in the Galápagos Islands and Other Ecuadorian Regions

Abstract: Torulaspora delbrueckii Flower Trichosporon asahii Rotten Wood Candida carvajalis Insecta Cryptococcus humicola Excrement Debaryomyces hansenii Rotten vegetal Hanseniaspora meyeri Fruit Rhodotorula glutinis Exudate Candida orthopsilosis Leaf Candida saopaulonensis Fungus Sugar cane mill (a) Biodiversity-The Dynamic Balance of the Planet 216 SPECIES SUBSTRATE SPECIES SUBSTRATE

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…The region features different types of vegetation, ranging from dense forests to savannahs and mountain refuges. Several works have been published on the yeast diversity in Amazonian rainforest biomes (Barriga et al, 2014;Barros et al, 2023;Cadete et al, 2012;Guamán-Burneo et al, 2015;Jacques & Casaregola, 2019;James et al, 2009James et al, , 2013Lopes et al, 2018;Matos et al, 2021;Mok et al, 1984;Morais, Rosa, et al, 1995;Neves et al, 2006;Vital et al, 2001). Most of these works show that the Amazonian rainforest biome is a vast source of novel yeasts.…”
Section: Amazonian Rainforestsmentioning
confidence: 99%
“…The region features different types of vegetation, ranging from dense forests to savannahs and mountain refuges. Several works have been published on the yeast diversity in Amazonian rainforest biomes (Barriga et al, 2014;Barros et al, 2023;Cadete et al, 2012;Guamán-Burneo et al, 2015;Jacques & Casaregola, 2019;James et al, 2009James et al, , 2013Lopes et al, 2018;Matos et al, 2021;Mok et al, 1984;Morais, Rosa, et al, 1995;Neves et al, 2006;Vital et al, 2001). Most of these works show that the Amazonian rainforest biome is a vast source of novel yeasts.…”
Section: Amazonian Rainforestsmentioning
confidence: 99%
“…In 1976, Porter (1976) determined that ~30 % of all vascular plant species found in the Galápagos have a Neotropical origin. Remarkably in their more recent study, Carvajal Barriga et al (2014) identified that 31 % of the yeast species isolated on the Galápagos Islands were also found on mainland Ecuador. This would indicate that plant dispersal may have played an important role in the dispersal of yeast species from the mainland to the archipelago.…”
mentioning
confidence: 94%
“…An ecological analysis of the Ecuadorian yeast strains registered in the CLQCA database was performed recently in order to develop a simple mathematical model for calculating how well individual yeast species have adapted to the differing habitats found in Ecuador (Carvajal Barriga et al , 2014). In this study, a set of 881 yeast strains, representing 104 species, was analysed using a mathematical approach which focused on the number of different natural regions of Ecuador each species was found to colonize as well as the number of different types of substrate from which they had been isolated.…”
mentioning
confidence: 99%
See 2 more Smart Citations